THE EFFECT OF GOOD CORPORATE GOVERNANCE IMPLEMENTATION ON COMPANY PERFORMANCE - Silaban, Lisda; Suhendi, Suhendi; Nasution, Anggi Pratama (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
The purpose of this study is to prove the application of good corporate governance to company performance. This research uses quantitative research. The data analysis technique used is the classical assumption test, multiple linear regression test, and the coefficient of determination (Adjusted RSquare). The basis for sampling in this study using purposive sampling with a total sample of 7companies in the food and beverage sub-sector listed on the IDX. The resultsshowed that the independent board of commissioners had a significant effect oncompany performance with a tcount of 6.415 with a significance level of 0.000. Managerial ownership has a significant effect on company performance with atcount of 2.741 with a significance level of 0.012. Institutional ownership has asignificanteffecton company performance with at countof3,567 with asignificance level of 0.006. Taken together,the independent board of commissioners,management ownership and institutional ownership have asignificant effect on company performance with a value of Fcount of 14,304 whileF table is 2,874 and a significance level of 0.027. This can be seen in the results of the coefficient of determination (AdjustedRSquare), which means that the dependent variable that can be presented by the independent variable is 64.4%. While the remaining35.6% is presented by other variables thatare not included in theregression model.